1961
DOI: 10.1042/bj0780246
|View full text |Cite
|
Sign up to set email alerts
|

The absorption spectra, magnetic moments and the binding of iron in some haemoproteins

Abstract: This suggests that if 'complexes' are prepared in which a large drop in the intensity of this band is observed, then, in all probability, an attack has taken place on the porphyrin ring rather than a simple change in the coordination to the iron (see following paper). The m-and fl-bands are more intense in low-spin than in high-spin complexes (see Table 1). The intensity of the oband in low-spin complexes is very dependent on Vol. 78 247

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
0

Year Published

1964
1964
2014
2014

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 199 publications
(32 citation statements)
references
References 11 publications
4
28
0
Order By: Relevance
“…A) are rather intense. This is in contrast with aquomet Fe(III) Mb spectrum where the α (ε 580 = 2.5 1/(mM cm)) and β (ε 530 = 7.5 1/(mM cm)) peaks are observed as obscure inflectional bands . Because a good correlation between the appearance of the α and β bands and the dominance of low‐spin state of the metal center is well established in hemoprotein , the visible spectrum in Fig.…”
Section: Resultsmentioning
confidence: 84%
“…A) are rather intense. This is in contrast with aquomet Fe(III) Mb spectrum where the α (ε 580 = 2.5 1/(mM cm)) and β (ε 530 = 7.5 1/(mM cm)) peaks are observed as obscure inflectional bands . Because a good correlation between the appearance of the α and β bands and the dominance of low‐spin state of the metal center is well established in hemoprotein , the visible spectrum in Fig.…”
Section: Resultsmentioning
confidence: 84%
“…This has been demonstrated nicely in a large number of hemoprotein derivatives (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). Our investigation of the absorption and MCD spectral behavior and of the magnetic susceptibility of the ferric N-HBPT complexes has shown that such correlation may be extended to model system studies (15).…”
Section: Introductionmentioning
confidence: 74%
“…Bands at 630 nm (E ¼ 55) could be due to 6 A 1g ! 4 T 1g transition and that at 412 nm (E ¼ 50) may be assigned [11] [12]. This complex shows broad asymmetric bands in the region 680 nm (E ¼ 50) and at 512 nm (E ¼ 250) assignable to 2 B 1g !…”
Section: Electronic Spectral Studies and Magnetic Behaviormentioning
confidence: 97%